A novel adsorption heat pump cycle: Cascaded mass recovery cycle - Quanwen Pan (2018)
© 2018 Elsevier Ltd and IIR Using mass recovery process can significantly improve the adsorption heat pump (AHP) system performance. A cascaded mass recovery cycle using multiple mass recovery process is proposed and studied. A theoretical calculation of silica gel–water AHP using different kinds of AHP cycle is performed and the results based on silica gel–water AHPs show that COP/CAQ of cascaded mass recovery cycle is superior to that of basic cycle or conventional mass recovery cycle. In other words, performance of AHP can be significantly improved by cascaded mass recovery cycle. Besides, cascaded mass recovery cycle is suitable for strict conditions of low heat source temperature, high heat sink temperature and low evaporation temperature, and its stage number of mass recovery is suggested to be less than 4 for convenient uses. Combined system of multi-stage and cascaded mass recovery cycle can overcome the disadvantages of high complexity and equipment cost and make the system more efficient and convenient.